Pleurotus giganteus (Berk.) Karunarathna & K.D. Hyde: nutritional value and in vitro neurite outgrowth activity in rat pheochromocytoma cells - Phan, C.W.; Wong, W.L.; David, P.; Naidu, M.; Sabaratnam, V. (2012)
BACKGROUND: Drugs dedicated to alleviate neurodegenerative diseases like Parkinson's and Alzheimer's have always been associated with debilitating side effects. Medicinal mushrooms which harness neuropharmacological compounds offer a potential possibility for protection against such diseases. Pleurotus giganteus (formerly known as Panus giganteus) has been consumed by the indigenous people in Peninsular Malaysia for many years. Domestication of this wild mushroom is gaining popularity but to our knowledge, medicinal properties reported for this culinary mushroom are minimal. METHODS: The fruiting bodies P. giganteus were analysed for its nutritional values. Cytotoxicity of the mushroom's aqueous and ethanolic extracts towards PC12, a rat pheochromocytoma cell line was assessed by using 3-[4,5-dimethythiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Neurite outgrowth stimulation assay was carried out with nerve growth factor (NGF) as control. To elucidate signaling mechanisms involved by mushroom extract-induced neurite outgrowth, treatment of specific inhibitor for MEK/ERK and PI3K signalling pathway was carried out. RESULTS: The fruiting bodies of P. giganteus were found to have high carbohydrate, dietary fibre, potassium, phenolic compounds and triterpenoids. Both aqueous and ethanolic extracts induced neurite outgrowth of PC12 cells in a dose- and time-dependant manner with no detectable cytotoxic effect. At day 3, 25 μg/ml of aqueous extract and 15 μg/ml of ethanolic extract showed the highest percentage of neurite-bearing cells, i.e. 31.7 ± 1.1% and 33.3 ± 0.9%; respectively. Inhibition treatment results suggested that MEK/ERK and PI3K/Akt are responsible for neurite outgrowth of PC12 cells stimulated by P. giganteus extract. The high potassium content (1345.7 mg/100 g) may be responsible for promoting neurite extension, too. CONCLUSIONS: P. giganteus contains bioactive compounds that mimic NGF and are responsible for neurite stimulation. Hence, this mushroom may be developed as a nutraceutical for the mitigation of neurodegenerative diseases.